1960
DOI: 10.1002/hlca.19600430412
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazol‐Derivate und verwandte Heterocyclen III. Synthese von 1‐Aminoalkyl‐2‐nenzyl‐nitro‐benzimidazolen

Abstract: The synthesis of a series of 1‐aminoalkyl‐2‐benzyl‐nitro‐benzimidazoles is described. Many of the 5‐nitro‐benzimidazoles prepared show strong analgesic activity. 1‐(β‐Diethylamino‐ethyl)‐2‐(p‐ethoxy‐benzyl)‐5‐nitro‐benzimidazole (XXXVIII) is 1000 times as potent as morphine and therefore the most active analgesic known until now.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
59
0
1

Year Published

1981
1981
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 5 publications
12
59
0
1
Order By: Relevance
“…The obtained data revealed that isotonitazene has a high potency (EC 50 of 11.1 nM) and efficacy (E max 180% of that of the reference compound used in this assay, hydromorphone), indicating that this compound is a strong opioid (which is also in good correspondence with data previously reported in the literature 16,34,35 ). These values are even slightly higher than those we obtained for the known potent E max = 155% (95%CI: 149-161), unpublished results).…”
Section: Pharmacological Evaluation Of Isotonitazene In Vitrosupporting
confidence: 87%
See 2 more Smart Citations
“…The obtained data revealed that isotonitazene has a high potency (EC 50 of 11.1 nM) and efficacy (E max 180% of that of the reference compound used in this assay, hydromorphone), indicating that this compound is a strong opioid (which is also in good correspondence with data previously reported in the literature 16,34,35 ). These values are even slightly higher than those we obtained for the known potent E max = 155% (95%CI: 149-161), unpublished results).…”
Section: Pharmacological Evaluation Of Isotonitazene In Vitrosupporting
confidence: 87%
“…We therefore hypothesized that the obtained powder sample was a salt, most likely of inorganic origin, given the lack of additional signals in the 1 H and 13 C spectrum. A melting point determination gave a mp of 174 C, indicating that the obtained compound is a HCl salt, as this is in line with the reported mp of 172-173 C. 35 From all the above-mentioned analyses, we concluded that the powder sample that was obtained online is of high purity.…”
Section: Nmr and Melting Point Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…Scheme 10 Reaction of 1,2-Diaminoarenes with Imidates [105,114,115,118,492] [118] H Cl H MeOH 55 [118] H Cl Cl MeOH 67 [118] H Me H DME 60 [118] Me H H MeOH 90 [118] Ethyl 2,4-Dinitrophenylacetimidate Hydrochloride: [114] To 2,4-dinitrophenylacetonitrile (20.7 g, 0.10 mol) in dry CHCl 3 (200 mL) was added EtOH (6 mL). The soln was cooled to 0 8C and then saturated with dry HCl during 0.5 h. After standing for 12 h at 0 8C, the colorless crystalline product was filtered and washed with dry CHCl 3 ; yield: 25 g (86%); mp 181 8C.…”
Section: With Formation Of 1-2 and 2-3 Bondsmentioning
confidence: 99%
“…1,4,5'-Trisübstitüe-2-Benzilbenzimidazol Türevleri. 5 Antibakteriyel aktiviteleri incelenecek olan bileşiklerin alkoldeki steril çözeltilerinden, her bakteri için hazırlanmış serinin ilk tüpüne 400 g/ml ) olacak şekilde ilave edilip, tüpten tüpe aktarılımlarla 10 dilusyon (400, 200, 100, 50, 25, 12,5, 6.2, 3.1, 1.5, 0. 7 g/ml) hazır-zırlandı.…”
Section: Mikrobiyolojik çAlışmalarunclassified